Wilson’s disease-associated gut dysbiosis: novel insights into microbial functional alterations, virulence changes, and resistance markers - Wei, Taohua; Qian, Nannan; Wang, Han; Song, Yuqi; Wang, Weiqi; Li, Yangyang; Zhao, Zihao; Xu, Fulin; Yang, Wenming (Frontiers in Microbiology, 2026)
BackgroundAlthough the gut microbiota is associated with a variety of metabolic, inflammatory, and neurological disorders through microbial dysbiosis, current studies on the gut microbiota in Wilson’s disease (WD) remain limited. Critical gaps exist in understanding the roles of key functional microbial factors in WD pathogenesis, which hinders the acquisition of mechanistic insights into this disease.ObjectiveThis study aims to characterize alterations in the gut microbiome associated with WD, with a particular emphasis on virulence factors (VFs) and antibiotic resistance genes (ARGs), as well as functional mobile genetic elements (MGEs), in order to elucidate their potential roles in disease progression and clinical manifestations.MethodsWe analyzed fecal samples from 37 patients with WD and 33 healthy controls (HCs) using metagenomic sequencing, with a specific focus on examining virulence gene profiles and antibiotic resistance patterns and MGE composition in relation to liver function markers.ResultsBeta diversity analysis revealed significant differences in the gut microbial community structure between patients with WD and HCs, and a distinct set of microbial taxa was identified that showed significant associations with clinical indicators. A gut microbial co-occurrence network identified key species playing central roles in the microbial community structure, including Prevotella stercorea, Firmicutes bacterium CAG 110, Bacteroides salyersiae, Lactococcus petauri, Streptococcus cristatus, Actinomyces sp. HMSC035G02, and Streptococcus viridans. Widespread functional dysbiosis was detected across multiple biological levels in patients with WD, with significant correlations identified between these microbial alterations and clinical indicators. Significant disruptions were identified in key metabolic pathways, including the Pentose Phosphate Pathway, Pyruvate Metabolism, and Starch and Sucrose Metabolism, which were associated with the dysregulation of carbohydrate-active enzymes (CAZymes). These alterations showed significant correlations with clinical markers of liver dysfunction (e.g., procollagen III N-terminal peptide PIIINP, aspartate transaminase/alanine transaminase AST/ALT). A total of 54 virulence factor (VF) genes exhibited differential abundance in WD, with 36 genes depleted and 18 enriched. Notably, these included colibactin genes (clbB, clbH) from Escherichia coli and type IV secretion system genes (aec19, pilB). These VFs were significantly associated with indicators of liver function (e.g., bilirubin levels) and coagulation abnormalities. Among the detected antibiotic resistance genes (ARGs), 21 exhibited disease-specific patterns in WD, notably tetQ (encoding tetracycline resistance), ErmB (conferring macrolide resistance), and cfxA6 (mediating cephamycin resistance). Furthermore, ARG profiles were associated with Bifidobacterium enrichment and showed significant correlations with lipid metabolism markers [e.g., triglycerides (TG), high-density lipoprotein cholesterol (HDL-C)]. Critically, we identified significant enrichment of 60 functional mobile genetic elements (MGEs) in WD, spanning categories involved in DNA replication/repair, phage activity, and conjugative transfer, indicating heightened genomic plasticity and horizontal gene transfer potential. Strikingly, correlation network analysis revealed strong and specific co-occurrence between key ARGs (e.g., ErmX) and defined suites of MGEs, suggesting MGE-facilitated dissemination of resistance determinants.ConclusionWilson’s disease (WD) patients exhibit significant alterations in gut microbial community structure and functional dysbiosis, wherein the enrichment of virulence genes (such as colibactin genes clbB/clbH) and the specific antibiotic resistance genes (such as tetQ and ErmB), and the activation of mobile genetic elements are closely associated with clinical indicators including liver function impairment, coagulation abnormalities, and lipid metabolism disorders.